Alginate Lyase and Ciprofloxacin Co-Immobilization on Biopolymeric Microspheres for Cystic Fibrosis Treatment - Islan, German Abel (2013)
A new formulation is described based on biopolymeric microspheres containing alginate lyase (AL) and ciprofloxacin (Cip) for sustainable oral delivery in CF patients. Alginate (ALG) and high-methoxyl pectin (HMP) are selected as the biopolymers to develop a composite matrix. ALG microspheres coated with HMP and ALG-HMP blend are gelled in water/organic solvents mixtures, obtaining Cip encapsulations from 46.0 to 100.0%. ALG-HMP shows a Cip sustainable release profile and is able to encapsulate 90.0% of AL, showing 76.0% enzyme activity after release under simulated intestinal conditions. The developed system is a promising delivery carrier to treat chronic infection of Pseudomonas aeruginosa and to reduce the viscoelasticity of the mucus accumulated into intestine of CF patients.